NITRIDING IN A LOW-TEMPERATURE GAS ENVIRONMENT AND OXIDATION OF THE FORMED NITRIDE LAYER IN WATER VAPOR - Sh. A. Berdiev (Web of Journals Publishing, 2025)
The article examines the structural and phase changes in surface diffusion nitride-oxide coatings obtained during nitriding in a gas environment followed by oxidation of ferrite-pearlite steels in water vapor, as well as the influence of phase changes on the corrosion properties.
Keywords: Ferrite, pearlite, nitriding, oxidation, diffusion coating, nitride layer, corrosion resistance.